The Gauge-Higgs legacy of the LHC Run II - Biekötter, Anke; Corbett, Tyler; Plehn, Tilman (Arxiv, 2018)
We present a global analysis of the Higgs and electroweak sector based on LHC Run II and electroweak precision observables. We show which measurements provide the leading constraints on Higgs-related operators, and how the achieved LHC precision makes it necessary to combine rate measurements with electroweak precision observables. The SFitter framework allows us to include kinematic distributions beyond pre-defined ATLAS and CMS observables, independently study correlations, and avoid Gaussian assumptions for theory uncertainties. These Run II results are a step towards a precision physics program at the LHC, interpreted in terms of effective operators.
Identifizierung der Ressource nach: Last revised 10 Apr 2019
Gesehen am 27.11.2020